Vascular Protective Effect and Its Possible Mechanism of Action on Selected Active Phytocompounds: A Review - Nur Aqilah Kamaruddin; Muhammad Nazrul Hakim Abdullah; Jun Jie Tan; Vuanghao Lim; Lai Yen Fong; Siti Aisyah Abd Ghafar; Yoke Keong Yong (Hindawi, 2024)
Hindawi Evidence-Based Complementary and Alternative Medicine Volume 2022, Article ID 3311228, 17 pages